The History of the Telephone - Casson, Herbert Newton, 1869-1951 (Salt Lake City, UT : Project Gutenberg, 1997)
"The History of the Telephone" by Herbert Newton Casson is a historical account likely written in the early 20th century. The book chronicles the fascinating development of the telephone, focusing on key figures such as Alexander Graham Bell, who is credited with its invention. As the narrative unfolds, it delves into the challenges and triumphs faced by Bell and his contemporaries during the initial creation and eventual commercialization of the telephone. The opening of the book introduces readers to the context in which the telephone was invented, highlighting the initial skepticism it faced in 1875. Herbert Newton Casson begins with Bell's breakthrough in a Boston machine shop, capturing the moment when he successfully transmitted sound over a wire for the first time. The text describes Bell's dedication to the project informed by his family's legacy in the study of speech and communication. It depicts the struggles and successes he experienced while surrounded by doubts from the public and competitors alike. Furthermore, Bell$1 (Bs relationship with his mentor, Thomas Watson, and his eventual marriage to Mabel Hubbard adds a personal dimension to Bell's professional journey. Overall, the beginning sets the stage for an engaging exploration of the telephone's invention and its profound impact on society. (This is an automatically generated summary.)s
Release date is 1997-02-01
Produced by Charles Keller, and David Widger
Keywords: Telephone -- History